Developing “SEEY“ Android-Based Game for Learning English Grammar: Research and Development - Sari, Hesty Puspita; Maulidyah, Silvi Nuril; Aini, Miza Rahmatika (STAI Miftahul Ula Nganjuk, 2022)
The study's goal is to create a “SEEY” android-based game for learning grammar with eighth-grade junior high school students. In this research, the research and development method is utilized (R and D). The study's emphasis was on 30 pupils from a random school in Blitar Regency, including six teachers and students from SMPN 1 Sutojayan, SMPN 1 Talun, and SMPN 1 Kanigoro. In addition to interviews, observations, and documents, this study also used a quantitative approach. the method of creating